Development of Differentiated Interactive Media to Encourage Student’s Number Sense - Nasrilia, Yonanda Kumala; Akmal, Ajril; Rif’ah, Zahrotur; Sasongko, Dimas Femy (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3189, 2024)
Number Sense ability is crucial to have as a basis for students' knowledge in solving numeracy problems. The use of learning media with number sense material content is very necessary today. Another problem arises in the variation of students' learning styles that require differentiated media to meet all needs. This study aims to develop differentiated learning media with number sense content. This research is research and development (R&D), where this study uses the ADDIE development model. This research was conducted at MTs Sunan Kalijogo Malang with a total of 36 students as subjects. The data obtained from the validation sheet is divided into qualitative and quantitative data which are analyzed to determine the feasibility of the learning media developed. The results of the media evaluation show an average percentage of 86.3%, with the category "Very Feasible". The question aspect obtained an average percentage of 84.5%, also with the category "Very Feasible". In addition, the results of the practicality questionnaire involving 36 students gave an average practicality percentage of 87.1%, also in the "Very Feasible" category. Thus, seeing the assessment results indicates that the developed learning media is very feasible to be implemented in the classroom learning process as a form of implementing the merdeka curriculum.